Effect of temperature on golf ball dynamics - Allen, T.; Bowley, P.; Wood, P.; Henrikson, E.; Morales, E.; James, D. (Procedia Engineering, 2012)
Golf is played at a range of temperatures. The aim of this research was to determine the effect of temperature on golf ball dynamics. Normal impact testing at speeds up to 48 m·s-1 was conducted at ball temperatures of -0.8 °C, 22 °C and 35.9 °C. Golf balls were projected onto a fixed rigid surface and inbound and rebound velocity, impact duration and maximum deformation were measured using a high-speed video camera. Coefficients of restitution, impact durations and maximum deformations were found to increase with temperature. A finite element model of the golf ball was produced using Ansys/LS-Dyna and the dynamic response corresponding to each temperature was obtained by systematically adjusting the material properties of the core. Changing golf ball dynamics with temperature has implications on approval test procedures as well as the development of balls and clubs. This research is the first step in a process for determining the effect of temperature on a golf drive.